A study on determinants of dividend policy in Sarawak based public listed companies - Mohamad Haniz, Bin Osman (Univerisiti Malaysia Sarawak (UNIMAS), 2012)
This study attempts to contribute to a controversy on the issue ofdividend policy among the financial community by examining the determinants of dividend policy for Sarawak based companies listed in the Bursa Malaysia. A sample of 13 firms was selected for the period 2002 to 2010 with 108 observations is included in the analysiV The financial data of these companies was analyzed by regressing the net income, free cash flow, total debt, total asset to the dividend yield Based on the results, all selected independent variables had indicated a significant relationship with dividend yield and considered to be the important determinants in the study. A positive association with dividend yield had only been found in the net profit which also consistence with the prediction in the developed hypotheses. Two variables which are the free cash flow and total asset have shown a negative association with dividend yield and inconsistent with the positive sign predicted in the hypotheses.